Debrecen szülötte, egyetemünk diákja és tanára, a 20. század kiemelkedő geológusa - Kozák, Miklós; McIntosh, Richard (Gerundium, 2017)
Native of Debrecen, Student and Professor of our University, Significant Geologist of the 20th Century: Dr. Vilma Fux Székyné (1916–2006). Dr. Vilma Széky-Fux, an exceptional scientist of the 20th century, geologist and professor with Széchenyi Prize was born in Debrecen 100 years ago and passed away in Budapest 10 years ago. She carried out successful education and research at two universities contributing to geology and expert training with useful inventions and valuable works at a time of war and regime changes. She was member of numerous national and several international scientific boards and her results were recognised abroad as well. She worked hard in aspiring student research and refereeing the results of colleagues working for scientific degrees. Her activity as an organizer, presenter and leader in the Hungarian Geological Society was outstanding. Her work was always highly respected as reflected by her prizes. The life and works of Professor Széky-Fux should stand as an example for all of us.